PERADILAN AGAMA DALAM SISTEM HUKUM INDONESIA - Martius, A. Havizh (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
The political influence of the law against the existence and position of Religious Courts in Indonesia marked by legal products on which the existence and position of the Religious Courts. The philosophical basis of the existence of the Religious Courts in Indonesia are the values of Pancasila embraced by the Indonesian people, especially the first principle